The use of PCMs for free cooling in buildings - Xu, Haipeng (2019)
The construction of high-rise buildings has become synonymous with growth and economic prosperity. However, the acceleration in architectural development of China has significantly contributed to the alarming state of environmental disruption. This impact has arisen from land use, energy consumption and the use of other resources such as materials and water, due to the demand for improved living standards and comfort by occupants. EU countries are not strangers to the effects that construction has on the environment, with over 40% of the total final energy consumption by buildings accounted for by the EU. China’s building sector currently accounts for 32.8% of its total energy use, which must not be taken lightly given the massive population of China as well as the rapid rate at which buildings are being constructed. This in turn produces about 50% of global CO2 emissions as well as various other environmentally damaging pollutants (that contribute to global warming). Renewable energy sources include hydropower, wind energy and solar energy or any other new passive cooling or heating technologies. Some of these methods have already widely been used in the EU and China. From the literature, the use of phase-change materials (PCMs) has been shown to help in cooling buildings. Thus, the present research aims to develop new PCM systems to obtain comfortable and healthy conditions in building spaces by reducing any unwanted heat and reducing energy consumption. It will also help with reducing CO2 emissions and minimizing the effects of climate change. Following a literature review and research planning, three different passive PCM systems were designed, and an active PCM slurry cooling pipe system was designed, investigated, modelled then tested under fixed laboratory conditions. Finally, each case was simulated, and the results were compared. The active PCM slurry cooling pipe system was proven the best cooling capacity among the PCM cases. To deepen the investigation, the active PCM pipe system was simulated in a typical building under the real climate conditions. The modelling results show that PCM pipe system helps to reduce the room temperature, the use of PCM pipe system can remain the room temperature in the comfortable temperature interval (23–28°C) for 7 days. In conclusion, the PCM can effectively improve the indoor comfort of the building and reduce the energy consumption of air conditioner system. Between the passive PCM system and active PCM system, the latter demonstrated better performance, and it also had the good results in cooperation with an air conditioner.